2020
DOI: 10.1093/mnras/staa109
|View full text |Cite
|
Sign up to set email alerts
|

A broad-band look of the accreting millisecond X-ray pulsar SAX J1748.9−2021 using AstroSat and XMM–Newton

Abstract: SAX J1748.9-2021 is a transient accretion powered millisecond X-ray pulsar located in the Globular cluster NGC 6440. We report on the spectral and timing analysis of SAX J1748.9-2021 performed on AstroSat data taken during its faint and short outburst of 2017. We derived the best-fitting orbital solution for the 2017 outburst and obtained an average local spin frequency of 442.361098(3) Hz. The pulse profile obtained from 3-7 keV and 7-20 keV energy bands suggest constant fractional amplitude ∼ 0.5% for fundam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
3
10
0
Order By: Relevance
“…Residuals around 30 keV due to the Xenon calibration edge (Antia et al 2017) were observed in the LAXPC20 spectra and were modeled using a Gaussian. A similar feature has also been found in the LAXPC spectra of other sources (see e.g., Sharma et al 2020;Banerjee et al 2020). We also added a larger systematic (3%) value to account for uncertainties in response calibration over such a wide energy band 4-70 keV (see e.g., Mudambi et al 2020).…”
Section: Spectral Analysis and Resultssupporting
confidence: 79%
“…Residuals around 30 keV due to the Xenon calibration edge (Antia et al 2017) were observed in the LAXPC20 spectra and were modeled using a Gaussian. A similar feature has also been found in the LAXPC spectra of other sources (see e.g., Sharma et al 2020;Banerjee et al 2020). We also added a larger systematic (3%) value to account for uncertainties in response calibration over such a wide energy band 4-70 keV (see e.g., Mudambi et al 2020).…”
Section: Spectral Analysis and Resultssupporting
confidence: 79%
“…We estimated the magnetic field strength to lie between 2.7×10 8 < B < 2.5×10 9 G, for the disc truncating between 31 < R in < 111 km. This limit on the magnetic field is consistent with the typical limit of magnetic field for the NS LMXBs (B 10 9 G) and AMXPs (Cackett et al 2009;Mukherjee et al 2015;Ludlam et al 2016;Sharma et al 2020).…”
Section: Discussionsupporting
confidence: 87%
“…AstroSat science instruments, including SXT, are ideal to study various spectral and timing properties of neutron star LMXBs, and their evolution. For example, the combined spectra from AstroSat (SXT+LAXPC) and XMM-Newton (EPIC-PN) observations of the neutron star LMXB SAX J1748.9-2021 suggested the presence of reflection features (Sharma et al, 2020). Fig.…”
Section: Neutron Star Low-mass X-ray Binariesmentioning
confidence: 98%